The application and evaluation of adaptive hypermedia techniques in Web-based medical education - Muan Hong Ng; Wendy Hall; Pat Maier; Ray Armstrong (Association for Learning Technology, 2002)
This article discusses the design issues involved in delivering Web-based learning materials. An existing application in the medical domain - JointZone - is used to illustrate how personalization and an interactive environment can be incorporated into Web-based learning. This work applies the combination of an adaptive hypermedia, situated-learning approach and hypermedia linking concepts to facilitate online learning. A usability study was carried out on the work described and an evaluation was undertaken to measure the effect of personalization on various learning factors. The evaluation outcome was analysed subjectively and objectively. The results proved to be contradictory but, nevertheless, the work gives new insights into the use of technology to support learning